A 1D mean line model for centrifugal compressors with variable inlet guide vanes. Issue 1 (1st August 2019) - Dewar, Brett; Creamer, Mike; Dotcheva, Mariana; Radulovic, Jovana; Buick, James M.
Abstract : This paper considers a 1D in‐line analytical model for centrifugal compressors with variable inlet guide vanes. A theoretical 1D model is developed to predict the effect of varying the inlet guide vane angle at different rotational speeds. An iterative algorithm is presented, which provides a fast and efficient method for evaluating the performance of the compressor under different operating conditions. The results from the analytical 1D model are presented and compared to full 3D CFD (computational fluid dynamics) simulations. The simulations validate the assumptions used in the 1D model and show good agreement between the two approaches over a range of vane angles. Qualitatively, both demonstrate the same trends as the vane angle and rotational velocities are varied. Quantitatively, the pressure ratio was found to agree within 8% and the temperature gain to within 15%. The 1D model was then modified to introduce a 5% loss in the diffuser and this was found to improve the 1D model predictions, with the pressure within 2% of the CFD value.